The fourth industrial revolution :shaping a humane world? - Abdul Razak, Dzulkifli; Moten, Abdul Rashid (Academic Book Series, 2022)
The 4th Industrial Revolution (4IR) is a new chapter in human development, enabled by technological advancements commensurate with the First, Second, and Third Industrial Revolutions. The 4IR revolves around automation and data exchange, including cyber-physical systems, the internet of things (IoT), and cloud computing. 4IR, controlled by artificial intelligence and intelligent robots, will supplant people in specific sectors. These technologies reflect the interests and desires of their creators, and these technologies shape the lives of the people. In the words of Professor Avram Noam Chomsky, society reduces education to the requirement of the market. He opined that human beings have no intrinsic, moral, and intellectual nature in educational institutions so created. The emphasis is on the workforce, mind, and machine for the marketplace. Education so imparted is one without a soul leading to weak ethical norms and dangerous trust deficits in communities. Educators must investigate new and creative approaches to educational innovation to upgrade future learning. The need is for education with a soul. Education should develop students’ moral, civic, and creative capacities and prepare them for a livelihood and, more importantly, life. This chapter argues that educators must cultivate “double consciousness” to humanize technology through the bold vision of moderation and middle ground.